trans activation of the tumor necrosis factor alpha promoter by the human T-cell leukemia virus type I Tax1 protein. - Albrecht, H (1992)
In a cotransfection assay, the human T-cell leukemia virus type I Tax1 gene product specifically activated transcription from the mouse tumor necrosis factor alpha promoter. The activation patterns of 5' deletion mutants, artificial enhancer constructs, and point mutations in the promoter indicate that the major Tax1-responsive element is a site at position -655 which binds the NF-kappa B/rel and NF-GMa transcription factors.